Is Cancer Within Your Body? May Be, Yes! (Advancements in Homeopathic Research, 2022)
Cancer, a sleeping monster, a silent enemy, a tormentor, a terrorizer is always present in human body and even in animal life and you have to live with it as long as you can. You cannot live in this century and years to come without diseases and death. Any time or day in your life when you wake up in the morning with pain anywhere in the body (Chest, mouth, abdomen, head, extremities, etc.) and/or you find, a swelling, a lump, a boil, pustule, a small ulceration with itching and bleeding with burning, pains in the bone(s), etc., you have the chance to end up with that sleeping monster; Cancer. All depends on many factors, exciting or maintaining causes, so-called carcinogens, carcinogenic food, agents – smoking, chewing tobacco, chemicals, circumstances and even genetically in your life. Is it possible to eradicate CANCER from our bodies and on this Earth in future? No and never. Cancer is a history as old as history goes with the first human being on this Planet. Do you believe in the theory of Darwin of evolution of human beings? If yes? Then, what? He, the first human being (you may call him as Adam or Monkey man in Hindu or Bible or Koranic traditions) created by GOD (Nobody knows when)? As the progenitor of the human race was naked and wandering in woods/jungles for food and probably he was bruised, injured, itched, scratched, eruptions or boils appeared on his body. He might have applied saliva, or leaves of plants or juices of plants, applied or rubbed mud or something he did for his suffering. Was it cured with that or had remission or relieved or suppressed? Are we not descendants of that man? Yes, then what? We are born with oversensitiveness and sensitive to have variant skin diseases, cancer and other diseases dependent on environments, food, occupation, weather or any diseased condition etc. A long journey to find out when cancer began. How cancer started in humans and animals and got localized in parts of the body, skin, organ(s) and has effected systems followed by generalization of the whole body? Then, it means a systematic disease. The cause was the invisible force or dynamic force or Miasms in Homoeopathy. Discovery of Cancer and Cancer cells by Microscope: Are cancer cells the real cancer or many types of cancers of the body? Cancer cells are abnormal cells. How these abnormal cells were produced from normal cells? These abnormal cells have their individuality for migration and to establish a new colony (ies) of cancer. Let us call this process, metastasis. What is/were the reason or reasons? Cancer as we know is a disease caused by uncontrolled growth of cell(s). Was it division of cells? Was it mutations of cells and growth? Or What? Incredible disease is hiding in us and playing with us in strange ways. We have to go in past to explain the present. Is it possible? What to do?
Keywords: CANCER; cells; carcinogenic food; human race